The contribution of information and communication technologies to economic growth in nine OECD countries - Colecchia, Alessandra (OECD Publishing, 2003)
This paper compares the impact of ICT capital accumulation on output growth in Australia, Canada, Finland, France, Germany, Italy, Japan, the United Kingdom and the United States. The analysis uses a growth accounting framework and a newly compiled database of investment in ICT equipment and software based on the System of National Accounts 1993 (SNA93). It is found that over the past two decades, ICT contributed between 0.2 and 0.5 percentage point per year to economic growth, depending on the country. During the second half of the 1990s, this contribution rose to 0.3 to 0.9 percentage point per year
Keywords: Economics